Effects of green tea on iron accumulation and oxidative stress in livers of iron-challenged thalassemic mice - T. Saewong (2018)
Liver is affected by secondary iron overload in transfusions dependent β-thalassemia patients. The redox iron can generate reactive oxidants that damage biomolecules, leading to liver fibrosis and cirrhosis. Iron chelators are used to treat thalassemias to achieve negative iron balance and relieve oxidant-induced organ dysfunctions. Green tea (GT) (Camellia sinensis) catechins exhibit anti-oxidation, the inhibition of carcinogenesis, the detoxification of CYP2E1-catalyzed HepG2 cells and iron chelation. The purpose of this study was to investigate the effectiveness of GT in iron-challenged thalassemic mice. Heterozygous BKO type-thalassemia (BKO) mice (C57BL/6) experienced induced iron overload by being fed a ferrocene-supplemented diet (Fe diet) for 8 weeks, and by orally being given GT extract (300 mg/kg) and deferiprone (DFP) (50 mg/kg) for a further 8 weeks. Liver iron content (LIC) was analyzed by TPTZ colorimetric and Perl's staining techniques. Concentrations of liver reduced glutathione (GSH), collagen and malondialdehyde (MDA) were also measured. Dosages of the GT extract and DFP lowered LIC in the Fe diet-fed BKO mice effectively. The extract did not change any concentrations of liver glutathione, collagen and MDA in the BKO mice. Histochemical examination showed leukocyte infiltration in the nearby hepatic portal vein and high iron accumulation in the livers of the iron-loaded BKO mice, however GT treatment lowered the elevated iron deposition. In conclusion, green tea inhibits or delays the deposition of hepatic iron in regularly iron-loaded thalassemic mice effectively. This will prevent the iron-induced generation of free radicals via Haber-Weiss and Fenton reactions, and consequently liver damage and fibrosis. Combined chelation with green tea would be investigated in β-thalassemia patients with iron overload. © 2010 Bentham Science Publishers Ltd.